Factors Affecting Early Marriage in Kati Maju Village, Ketambe District, Southeast Aceh Regency - Rahmi, Hayati; Amirah, Asriwati; Nuraeni, Nuraeni; Ramadhani, Safitri (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
In Indonesia, the marriage rate always increases from year to year. In 2017 there were 1,936,934 people who married and the number increased to 2,016,171 people in 2018. The aim of the research was to determine the description of factors that influence early marriage in Kati Maju village, Ketambe subdistrict, Southeast Aceh district. This type of research uses observation methods related to early marriage. The data analysis technique used in this research is qualitative descriptive techniques, where all data is obtained from observation, interviews and documentation. The research results that cause early marriage are economic factors based on the economic needs that are most felt to be urgent in the family. Parents marry off their young children because parents have low awareness of the importance of their children’s education, so they prefer to stop their children from going to school because they think it is a waste of time and money. And social factors assume that unmarried children are a burden on the family and must bear shame. It is recommended that health workers provide education and outreach to families regarding the impact of early marriage on their reproductive health.